2016
DOI: 10.1007/s00213-016-4202-4
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, longitudinal study of sleep disturbance and comorbidity in opiate dependence (the ANRS Methaville study)

Abstract: Sleep disturbance is frequent among opioid-dependent patients. It can be regarded as an important signal of more complex psychiatric comorbidities such as suicidal risk and ADHD. However, sleep disturbance should not be considered an obstacle to methadone maintenance treatment (MMT) initiation or continuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 67 publications
1
12
1
1
Order By: Relevance
“…Moreover, several studies have reported a significant association between smoking and sleep problems, 49 , 50 and a prospective study also reported that opioid-dependent patients with severe nicotine dependence had a higher risk of severe sleep disturbance. 51 However, the present study did not find a significant association between nicotine use and CPSD. Further studies focusing on heroin users receiving MMT are needed to explore the association between nicotine use and sleep disturbance.…”
Section: Discussioncontrasting
confidence: 92%
“…Moreover, several studies have reported a significant association between smoking and sleep problems, 49 , 50 and a prospective study also reported that opioid-dependent patients with severe nicotine dependence had a higher risk of severe sleep disturbance. 51 However, the present study did not find a significant association between nicotine use and CPSD. Further studies focusing on heroin users receiving MMT are needed to explore the association between nicotine use and sleep disturbance.…”
Section: Discussioncontrasting
confidence: 92%
“…Third, sleep disorders could mediate the relationship between pain and suicide attempt/ideation. Although not observed in the present study, the association between sleep disorders and pain and suicide risk was highlighted in a previous study using Methaville trial data [46]. Fourth, physical pain could lead to suicide attempt/ideation through its interaction with social pain (hopelessness, loss of work and changing family role, as well as isolation due to pain), as both types of pain may share some underlying neurological mechanisms [47].…”
Section: Discussionmentioning
confidence: 53%
“…Relative to healthy controls (8.8%), significantly more individuals with OUD (80.6%) have ratings ≥5 on the Pittsburgh Sleep Quality Index, indicative of poor sleep quality (Hartwell, Pfeifer, McCauley, Moran-Santa Maria, & Back, 2014), which has also been verified objectively through polysomnography (PSG) testing (Kay, Eisenstein, & Jasinski, 1969; Kay, 1975; Xiao et al, 2010). Sleep disturbance is evident among patients who are newly enrolled into OMT (Burke et al, 2008; Nordmann et al, 2016), as well as long-term OMT patients (Stein et al, 2004). Longitudinal evaluations suggest sleep does not naturally improve over the course of methadone treatment (Nordmann et al, 2016; Peles, Schreiber, Hamburger, & Adelson, 2011) and that sleep may in fact worsen, with the development of central sleep apnea in some patients (Wang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%